Diagnostic features of tuberculosis meningitis a cross-sectional study - Pasco, Paul Matthew D.
Tuberculous meningitis (TBM) is considered to be the most common primary infection of the central nervous system in the Philippines; however it remains very difficult to diagnose as findings are non-specific. Hence we decided to determine if the following clinical and laboratory features are associated with the diagnosis of definite TBM: new-onset seizures; focal neurologic deficit; presence of PTB on chest X-ray; CSF pleocytosis with lymphocytic predominance; decreased CSF glucose; increased CSF protein. Adult patients with suspected TBM (headache, fever and sensorial change of at least 7 days duration) were enrolled in the study after informed consent was obtained. Baseline physical examination and diagnostic tests including CT scan of the head with contrast and CSF analysis for qualitative examination, AFB smear, TB culture and cryptococcal antigen detection were done and results collected prospectively. Definite TBM was defined as a positive AFP smear or positive TB culture or positive basal meningeal enhancement on CT contrast study. Odds ratios for the presence of each of the of the above features were then calculated. Logistic regression was then done to determine which of these, if any, were significantly associated with a diagnosis of TBM. A total of 91 patients were included in the study. Using the gold standard criteria mentioned above, 44 had definite TBM; but if subsequent clinical course and response to anti-Koch?s therapy are taken into account, 68 had a final diagnosis of TBM, while the rest had other diagnoses such as bacterial meningitis and cryptococcal meningitis. After logistic regression was performed, only abnormal CSF was associated with the diagnosis of TBM. In patients with possible TBM, only abnormal CSF was found to be associated with the diagnosis of TBM, with moderate sensitivity and specificity. In the absence of simple yet sensitive enough diagnostic criteria, a consensus definition of TBM also must be developed.